Parametric analysis of small scale cavity receiver with optimum shape for solar powered closed Brayton cycle applications. (25th July 2017) - Daabo, Ahmed M.; Ahmad, Abdalqader; Mahmoud, Saad; Al-Dadah, Raya K.
Highlights: The performance of small scale solar powered closed Brayton cycle has been proposed. The optimum shape of each receiver configuration has been, optically, achieved. The real flux distribution on the helical tube surface inside each receiver has been used. An enhancement in the thermal performance of studied cavity receivers has been achieved. Abstract: Day after day the interest in the renewable clean energy is increasing because of the enormous advantages that it has. One of the main forms for the renewable energy is the solar which has been used through power systems such as the Concentrated Solar Power (CSP), which shows a remarkable enhancement recently. The current study examines different arrangements of an open cavity receivers with an aperture area of 0.02835 m 2 and an average flux values ranged from 2.5 to 15 kW/m 2 . By employing an advanced ray tracing OptisWorks software, which uses the Monte-Carlo ray-tracing technique for predicting the flux distributions, to decrease the optical losses and computational fluid dynamic CFD analysis to minimize the thermal losses, the fluid exit temperature can be maximised. The exact values and distribution of the received irradiance by the surface area of each helical coil, inside the receiver shape, was subsequently transferred and used as an input parameter using the User Defined Function, UDF, in order to numerically simulate the fluid flow and calculate the amount of heat transfer to the working fluid through the CFD analysis. Different scenarios including each, the shape configuration, the reflector diameter, and the helical coil pitch has been intensively carried out in the study. Results showed that compared to 0.5D pitch value, the zero pitch showed better performance in both optically and thermally. Moreover, an enhancement up to around 7% in the overall thermal performance was achieved when the receiver aperture area was covered by glass. Finally, some analysis for closed Brayton cycle was considered and the results showed the 80% overall system efficiency is applicable if there is more than one application is integrated in the system.